(untitled) (Social and Environmental Law Journal, 2023)
The present article intends to analyze and reflect on the serious situation of the "mothers in prison", since it is an unknown issue to society or is avoided in the conversation circles due to the cruel reality. The objective of this study is to identify the inhumanity of the Brazilian prison system, especially in relation to women who are mothers and have the right to breastfeed and live with their children. The methodology used is deductive, by means of qualitative-bibliographical research of books and articles concerning the theme, in addition to legislative-doctrinal research. The research question is whether the minimal non-fulfillment of the rights of mothers with their children in adequate places inside the prison results in the lack of respect and exercise of the foreseen legal rights? In this sense, it is necessary the implementation of public policies, the performance of other entities and improvements in the physical structure for the care of women.